(untitled) (Innovative Technologica: Methodical Research Journal, 2023)
Critical reading generally refers to reading in a scholarly context, with an eye toward identifying a text or author’s viewpoints, arguments, evidence, potential biases, and conclusions. Critical reading means evaluating what you have read using your knowledge as a scholar. You may look at the quality of the writing, the quality of the research, and the persuasiveness of the arguments, among other things. Finally, critical reading is an active process by which a scholar rigorously and systematically questions the literature with the goal of assessing credibility and validity.